x(x+5)+1=(x+6)(x+6)

Simple and best practice solution for x(x+5)+1=(x+6)(x+6) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for x(x+5)+1=(x+6)(x+6) equation:


Simplifying
x(x + 5) + 1 = (x + 6)(x + 6)

Reorder the terms:
x(5 + x) + 1 = (x + 6)(x + 6)
(5 * x + x * x) + 1 = (x + 6)(x + 6)
(5x + x2) + 1 = (x + 6)(x + 6)

Reorder the terms:
1 + 5x + x2 = (x + 6)(x + 6)

Reorder the terms:
1 + 5x + x2 = (6 + x)(x + 6)

Reorder the terms:
1 + 5x + x2 = (6 + x)(6 + x)

Multiply (6 + x) * (6 + x)
1 + 5x + x2 = (6(6 + x) + x(6 + x))
1 + 5x + x2 = ((6 * 6 + x * 6) + x(6 + x))
1 + 5x + x2 = ((36 + 6x) + x(6 + x))
1 + 5x + x2 = (36 + 6x + (6 * x + x * x))
1 + 5x + x2 = (36 + 6x + (6x + x2))

Combine like terms: 6x + 6x = 12x
1 + 5x + x2 = (36 + 12x + x2)

Add '-1x2' to each side of the equation.
1 + 5x + x2 + -1x2 = 36 + 12x + x2 + -1x2

Combine like terms: x2 + -1x2 = 0
1 + 5x + 0 = 36 + 12x + x2 + -1x2
1 + 5x = 36 + 12x + x2 + -1x2

Combine like terms: x2 + -1x2 = 0
1 + 5x = 36 + 12x + 0
1 + 5x = 36 + 12x

Solving
1 + 5x = 36 + 12x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-12x' to each side of the equation.
1 + 5x + -12x = 36 + 12x + -12x

Combine like terms: 5x + -12x = -7x
1 + -7x = 36 + 12x + -12x

Combine like terms: 12x + -12x = 0
1 + -7x = 36 + 0
1 + -7x = 36

Add '-1' to each side of the equation.
1 + -1 + -7x = 36 + -1

Combine like terms: 1 + -1 = 0
0 + -7x = 36 + -1
-7x = 36 + -1

Combine like terms: 36 + -1 = 35
-7x = 35

Divide each side by '-7'.
x = -5

Simplifying
x = -5

See similar equations:

| 7=r^(1/2) | | 6x-3-5x=-13-5 | | 2cotx/sinx | | 35=x+(3x-1)+(2(2x-1)+2) | | M/10=4 | | 8x-7x-6=7-13 | | 10(x+2/15)=8(x-7/3) | | 35=x+(2x-1)+(4(2x-1)+2) | | 9x-16=3x+20 | | X/2=50 | | 4x-5=3x-3 | | -5=7x+1-6x | | 35=x+(2x-1)+(14(2x-1)+2) | | 115+5x=240 | | 3.5x+5=50.50 | | -15=-6r-1-2 | | 25x+57=232 | | M^(3/4)=27 | | 15x-17+2x=-34 | | 5x+9-4x=-1 | | 5x-1=4x-4 | | 6+3a+4a=-8 | | 5x-1=4x-1 | | 3x+9-2x=5 | | 440.2908=105.5668+25.748h | | 5-2[3x-4(5-x)]=6(7-x) | | 8y+15=7y-8 | | 3x+9-2=5 | | (1-14+x)/23=15 | | 4x^2=3x-2 | | 10y+7-4y=-5+6y+22. | | 1/x^2-1 |

Equations solver categories